Adsorption Characteristics of Different Adsorbents and Iron(III) Salt for Removing As(V) from Water - Josip Ćurko; Marin Matošić; Vlado Crnek; Višnja Stulić; Ivan Mijatović (Food Technology and Biotechnology, 2016)
The aim of this study is to determine the adsorption performance of three types of adsorbents for removal of As(V) from water: Bayoxide® E33 (granular iron(III) oxide), Titansorb® (granular titanium oxide) and a suspension of precipitated iron(III) hydroxide. Results of As(V) adsorption stoichiometry of two commercial adsorbents and precipitated iron(III) hydroxide in tap and demineralized water were fitted to Freundlich and Langmuir adsorption isotherm equations, from which adsorption constants and adsorption capacity were calculated. The separation factor RL for the three adsorbents ranged from 0.04 to 0.61, indicating effective adsorption. Precipitated iron(III) hydroxide had the greatest, while Titansorb had the lowest capacity to adsorb As(V). Comparison of adsorption from tap or demineralized water showed that Bayoxide and precipitated iron(III) hydroxide had higher adsorption capacity in demineralized water, whereas Titansorb showed a slightly higher capacity in tap water. These results provide mechanistic insights into how commonly used adsorbents remove As(V) from water.